2019
DOI: 10.2340/16501977-2532
|View full text |Cite
|
Sign up to set email alerts
|

A protocol for permissive weight-bearing during allied health therapy in surgically treated fractures of the pelvis and lower extremities

Abstract: Aftercare in surgically treated trauma patients with fractures of the pelvis and lower extremities has remained largely unchanged during the past 60 years. To optimize rapid clinical recovery and the restoration of function and functionality, permissive weight-bearing has been designed as a new aftercare mobilization regime, within the upper boundary of the therapeutic bandwidth, yet safe enough to avoid overloading. The aim of the present paper is to describe a comprehensive protocol for permissive weight-bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 26 publications
0
35
0
2
Order By: Relevance
“…This protocol is unchanged for 60 years and not based on evidence-based medicine (5). Recent studies have added evidence in support of the use of an early or permissive weight bearing protocol (4,28,29). According to the present study, the healthcare costs together with the productivity losses represent the majority of the total costs.…”
Section: Discussionmentioning
confidence: 57%
“…This protocol is unchanged for 60 years and not based on evidence-based medicine (5). Recent studies have added evidence in support of the use of an early or permissive weight bearing protocol (4,28,29). According to the present study, the healthcare costs together with the productivity losses represent the majority of the total costs.…”
Section: Discussionmentioning
confidence: 57%
“…Among these, 158 papers were finally considered for eligibility and 80 papers were finally included in the review. In severe pelvic injuries, there is an 80% chance of associated other intrapelvic lesions, 4,5 , thoracoabdominal injuries like ribs or stern fractures, pneumothorax, liver laceration, and splenic rupture, small or large intestine lesions, 6,7 and other local lesion involving soft tissues (over 72% of patients), rectum and sphincters (18 -64%), urethra (1,6 -25 %), bladder (neurogenic bladder, structural rupture), vagina, nerves, 8 as well as post-traumatic osteoarthritis (7 -40%) 9 , heterotopic ossification, 10,11 and ischemic necrosis of the femoral head. 9 Pelvic ring and acetabular fractures often present with perineal swelling of soft tissue, due to the hemorrhage that develops into the retroperitoneal space and flows dissecting fascial planes into the scrotum.…”
Section: Resultsmentioning
confidence: 99%
“…6 A previous systematic review of multidisciplinary rehabilitative interventions in patients with multiple trauma 24 and a recent paper highlighted the lack of guidelines for post-surgical rehabilitation in PF. 25 Early rehabilitation of the patient with PF may begin with prevention strategies, principally of skin ulcers, loss of Range of Movement (ROM), joint contractures and urogenital disorders. If allowed, patient's position should be changed every 2-3 hours with semisupine position and right and left side lying and low-air-loss bed must be used in patients with unstabilized fractures.…”
Section: Resultsmentioning
confidence: 99%
“…On average, our animals gained about 8.6% weight during this period, which also had an impact on bone healing. Recent studies have shown that the increase in load‐bearing by the fracture ideally takes place in parallel with fracture healing 39 Normal weight bearing stimulates bone healing, whereas activity above normal neither accelerates nor impairs this process. The function of muscles and joints around a fracture site seems to be an important stimulus to the bone‐healing‐process 40 …”
Section: Discussionmentioning
confidence: 99%